Perbedaan Kecerdasan Emosi pada Mahasiswa yang Diterima Melalui Jalur PMDK dan SNMPTN di Fakultas Kedokteran Universitas Sebelas Maret - Saputra, Bobbi Juni; Fanani, Moch; Murti, Bhisma (Nexus Pendidikan Kedokteran dan Kesehatan, 2012)
Background: Emotional Quotient (EQ) is an ability to manage emotional life with intel-ligence. Self-motivation is one of EQ factor. Students who were accepted through PMDK admission had been likely to be able to manage their emotional life since adolescence. The purpose of this research is to analyze the difference between medical students who were accepted through PMDK admission and SNMPTN entrance examination. Methods: This was an observasional analytic study with cross sectional approach, condeucted in April 2012 at Faculty of Medicine, Sebelas Maret University. Samples were selected using purposive random sampling method. EQ scores were measured using emotional quotients inventory questionnaire and statistically tested by Kolmogorov- Smirnov test for normality distribution and Mann-Whitney test using SPSS 17.0 program for Windows. Results: Result from Mann-Whitney test showed a significant mean difference of EQ scores (p < 0.001) between medical students who were accepted through PMDK admission (116.67 ± 5.24) and SNMPTN entrance examination (106.67 ± 7.12). Conclusions: This study found statistically significant difference of EQ scores between medical students who were accepted through PMDK admission and through SNMPTN entrance examination at Faculty of Medicine, Sebelas Maret University. The EQ scores of student accepted through PMDK admission was higher than those of student accepted through SNMPTN entrance examination. Keywords: Medical students accepted through PMDK admission, medical students accepted through SNMPTN entrance examination, emotional quotient.